Barriers to technology adoption in agriculture-based industry and its integration into technology acceptance model. (2018) - Kumari, Sneha; Jeble, Shirish; Patil, Yogesh B.
This paper attempts to develop a scale to overcome barriers to technology adoption. The study is unique, as it interlinks barriers of technology adoption with the technology acceptance model. For the present study, the barriers to technology adoption were extracted from the literature, and a survey of 150 agriculture-based industries was conducted. An exploratory factor analysis (EFA) was carried out to develop the scale for barriers. The study carried out for the present paper helps to extend prior research works on grouping several barriers to technology adoption. The significant barriers to technology adoption that have been grouped are finance and economy, industrial policy and research, complexity, knowledge, government, and technical skills. The groups have further been interlinked with the technology acceptance model. These groups, thus, help in the perceived usefulness and usage of technology. The study can be applied for developing a technology-based agriculture industry by working out some solutions for the barriers to technology adoption. The present paper can be useful for setting initiating establishing technology adoption in the industry.